Generalized Asymptomatic Nodulo-Ulcerative Lesions Without Systemic Symptoms in a Secondary Syphilis Patient Co-Infected with HIV - Maharani RH; Nugraha T; Sutedja E; Ruchiatan K; Usman HA; Achdiat PA (Dove Medical Press, 2023)
Retno Hesty Maharani,1 Tomi Nugraha,1 Endang Sutedja,1 Kartika Ruchiatan,1 Hermin Aminah Usman,2 Pati Aji Achdiat1 1Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Bandung, Indonesia; 2Department of Anatomical Pathology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Bandung, IndonesiaCorrespondence: Pati Aji Achdiat, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +62 81322750101, Email pati.aji.achdiat@unpad.ac.idAbstract: Syphilis is a sexually-transmitted disease with various clinical stages. Secondary syphilis manifestations may mimic other skin lesions. Patient co-infected with Human Immunodeficiency Virus (HIV), with CD4 cell counts of 200- 499 cells/mm3, often manifests an atypical cutaneous lesion, which may also occur as nodular or ulcerative lesions. Generalized nodulo-ulcerative lesions without systemic symptoms in secondary syphilis patients with HIV co-infection are rarely reported. A 22-year-old man presented with generalized asymptomatic multiple erythematous papules and plaques with scales, as well as nodular and nodulo-ulcerative lesions on the trunk, both arms, and both legs. His lesions spread progressively without the presence of any prodromal symptoms or adenopathy. He was previously diagnosed with HIV and is currently on antiretroviral medications, with a CD4 cell count of 388 cells/μL. His venereal disease research laboratories (VDRL) result was reactive (titer of 1:256). His Treponema pallidum hemagglutination assay (TPHA) result was also reactive (titer of 1:10,240). A skin biopsy was performed from the nodulo-ulcerative lesion on his back. Hematoxylin-eosin staining revealed a hyperplastic epidermis, a massive influx of plasma cells, and lymphocyte infiltration into the deep dermis, especially in the peri-adnexal, peri-vascular, and peri-muscular regions. The patient was diagnosed with secondary syphilis with HIV co-infection. He had no previous history of drug allergy. A single dose of 2.4 million units of benzathine penicillin G was administered. Almost all the lesions became hyperpigmented macules after two weeks and resolved completely after one month. His VDRL titer declined to 1:32 after three months. The various atypical lesions of secondary syphilis may lead to misdiagnosis and delayed treatment. The presence of multiple asymptomatic nodulo-ulcerative lesion without prodromal symptoms may indicate the presence of secondary syphilis, notably in patients co-infected with HIV. Therefore, knowledge of atypical cutaneous manifestations of secondary syphilis is warranted in order to treat patients accordingly.Keywords: secondary syphilis, human immunodeficiency virus, nodulo-ulcerative lesions